A cross-sectional study on etiopathology and clinical findings of Mulangaal vaadham among the inward patients in Siddha Teaching Hospital, Kaithady, Jaffna: Sumaiya B.K., Rifna A.R., Fasrina N.F., Inshafa T.F., Hakeema M.Z., Naseeba Ganam M.J., Divarjitha T., Sujeethasai K. and Thayalini T.* (Sri Lanka Journal of Indigenous Medicine (SLJIM), 2024)
Mulangaal vaadham (Knee Osteoarthritis) is one of the Vaadha disease. Pain, swelling and stiffness in knee joint are the important clinical features of this disease. This research was aimed to study about etiopathology and clinical findings of Mulangaal vaadham among the inward patients in Siddha Teaching Hospital, Kaithady, Jaffna. This was a hospital-based Descriptive Cross-Sectional Study. It was conducted among the thirty inward patients who were diagnosed with Mulangaal vaadham by Siddha physicians in Siddha Teaching Hospital, Kaithady, Jaffna. Data were collected by using Interviewer structured Questionnaire. Examination was done and recorded in the case record sheet. Collected data were processed and analyzed by using MS Excel. According to the study, 97% of the patients were above the age 50 and 77% of them were females. Obese and overweight were the causes of Mulangaal vaadham in 67% of the patients; prolonged standing and excessive walking were in 37% of the patients. Based on the results, 100% of the patients had pain in the knee joint. Joint stiffness and difficulty in walking were present in 87% of the patients. Identified signs were crepitus in 100% of the patients, tenderness in 83% of the patients, swelling and heat in 73% of the patients. Prolonged standing and walking increase the pain in all the patients. Cold climates and foods like bitter-gourd, pumpkin, plantain and long beans aggravates pain in 83% of patients. Vaadha-Pitta naadi was predominant in 77% of patients in morning and 93% in the afternoon and evening. Therefore, these findings show that Mulangaal vaadham may be caused due to vitiated Vaadham which is produced by Thaathu sheenam (Degenerative changes in bones of knee joint). However, similar studies should be conducted with higher number of the patients in future to make a firm conclusion.